Blend Time Measurement in the Confined Impeller Stirred Tank. Issue 8 (7th June 2019) - Jairamdas, Khilesh; Bhalerao, Akshay; Machado, Marcio Bezerra; Kresta, Suzanne M.
Abstract: An image processing technique is applied to measure the blend time in a confined impeller stirred tank (CIST). An acid‐base reaction is used to track mixing. The blend time is defined as the time taken to 95 % or 99 % of the pixels change color from purple to yellow. Six sets of impellers are employed: Rushtons, A310s, pitched‐blade turbines (PBTs; three different combinations of up‐ and down‐pumping), and Intermigs. Variation of the Reynolds number Re showed that the blend time becomes shorter with increasing Re and longer with higher viscosity. As Re drops below 225, compartmentalization becomes apparent and the decolorization percentage increases suddenly when the acid reaches each communication point between the impellers. Abstract : The blend time and macromixing performance were characterized for the confined impeller stirred tank in both turbulent and low transitional flow regimes. Six different impeller configurations were investigated and a formerly developed decolorization and image analysis technique was applied for the experiments. For tracking successful mixing, an acid‐base reaction was employed.